Cultivation of taioba in hydroponic system (ebb and flow) using different substrates - Costa, Adriana; da Silva, Ernani Clarete; de Almeida Carlos, Lanamar; Moreira Martins, Luma; Mascarenhas Maciel, Gabriel; Nunes de Mendonça, Thiago Fellipe (Scientia Plena, 2020)
Taioba is a plant species from the group of unconventional vegetables that has currently been introduced into the Brazilian diet. The objective of the present work was to study the technical feasibility of the cultivation of taioba in the hydroponic ebb and flow system and the influence of the substrate. The experimental design was in randomized blocks and the treatments consisted of 10 different substrates: (1) 60% sand + 40% coal powder; (2) 80% coconut fiber + 20% vermiculite vermiculite; (3) 80% Sand + 20% coal powder; (4) 70% sand + 30% humus; (5) coconut fiber; (6) 70% sand + 30% vermiculite; (7) 80% sand + 20% vermiculite; (8) sand; (9) commercial substrate Carolina® and (10) 50% sand + 30% humus + 20% vermiculite. The best results were obtained with treatments 2 and 9 for the number of leaves, plant height, stem diameter, transverse and longitudinal leaf diameters, dry and fresh root mass, and dry and fresh plant mass. Except for the total carotenoid contents, no statistical differences were observed for the physical-chemical characteristics. It was concluded that cultivation of taioba in the hydroponic ebb and flow system has technical feasibility. The substrate has influence in the technical feasibility.